RANCANGAN APLIKASI JASA EDITING TRAILER FILM UNTUK PENINGKATAN PROMOSI DIGITAL: Movie Trailer Editing Service, Digital Promotion, Digital Technology , Movie Trailer, Audience Interest - Susanto, Darex; Husaini, Alfayed (JURNAL AKADEMIKA, 2025)
In the film and digital content industry, movie trailers are a crucial element in enhancing the appeal and promotion of films. As technology advances and the production of films and digital content increases, the need for professional movie trailer editing services is growing. Fierce competition in this industry demands quality and creativity in trailers to capture attention.